2007
DOI: 10.3748/wjg.13.6396
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct pathways of p16 gene inactivation in gallbladder cancer

Abstract: AIM:To examine the mechanism of inactivation of the p16 gene in gallbladder cancer, and to investigate p16 alterations and their correlation with clinicopathological features. METHODS:Specimens were collected surgically from 51 patients with gallbladder cancer. We evaluated the status of protein expression, loss of heterozygosity (LOH), homozygous deletion and promoter hypermethylation using immunohistochemistry, microsatellite analysis, quantitative real-time polymerase chain reaction (PCR) and methylation-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…The use of methylation in the search for new biomarkers in GBC is a promising alternative since this epigenetic modification is an early, progressive and cumulative event in GBC. The methylation frequency of promoter regions of some important tumor suppressor genes, such as p16 CDH1 REPRIMO DAPK-1 and SEMA3B , is high in GBC [29,40,48,50,51,88], and has also been well documented in other cancers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of methylation in the search for new biomarkers in GBC is a promising alternative since this epigenetic modification is an early, progressive and cumulative event in GBC. The methylation frequency of promoter regions of some important tumor suppressor genes, such as p16 CDH1 REPRIMO DAPK-1 and SEMA3B , is high in GBC [29,40,48,50,51,88], and has also been well documented in other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This variation could be directly related to ethnic differences. Tadokoro et al [50] found a frequency of 73% of methylation in p16 in samples from Japan, and Takahashi et al [32] a frequency of 24% in samples from Chile. The age of the patients could also introduce variations in results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations